APPLICATION OF STEM-BASED BLENDED LEARNING TO THE COGNITIVE ABILITIES OF 11 AMBON STATE SENIOR HIGH SCHOOL STUDENTS - Wally, Pramita; Kubangun, Muhammad Tarmizi (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2023)
Background: Blended learning is a mixed learning model between face-to-face and online learning. The STEM-based blended learning model can guide and train students to think logically, critically, evaluatively, creatively in solving problems and making decisions related to dealing with life's problems by utilizing technology and applying it in real life. Methods: The type of research used was a pre-experimental design with one group pretest-posttest. The research was located at SMA Negeri 11 Ambon and was carried out on January 2022. The research subjects were 36 students in class XII MIA-4 at SMAN 11 Ambon in the 2021-2022 academic year. Results: The results of the study show that there is a fairly effective effect in improving cognitive outcomes in class XII students of SMA Negeri 11 Ambon. Conclusion: There is an influence of the application of blended learning with the STEM approach to increasing scientific literacy and cognitive abilities of class XII students of SMA Negeri 11 Ambon in the new normal period